The Role of Local Authorities in Protecting Hajj Pilgrims in Indonesia: A Legal Protection Perspective - Muchammad Shidqon Prabowo (Jurnal Daulat Hukum, 2026)
Indonesia, as the country with the world’s largest Hajj contingent, requires effective governance to ensure comprehensive legal protection for pilgrims. This study aims to analyze the roles of local authorities in Hajj protection, identify governance challenges, and formulate policy recommendations. This research employed a qualitative doctrinal legal approach combined with policy-oriented legal analysis and literature review. The analysis was based on Law Number 8 of 2019 concerning the Organization of Hajj and Umrah Pilgrimage, Law Number 23 of 2014 concerning Regional Government, Law Number 17 of 2023 concerning Health, Law Number 34 of 2014 concerning Hajj Financial Management, and Minister of Health Regulation Number 15 of 2016 concerning Health Istitha’ah for Hajj Pilgrims. The findings show that local authorities play important roles in health protection, financial facilitation, regulatory compliance, and institutional coordination. However, regulatory fragmentation, uneven regional capacity, and weak coordination reduce implementation effectiveness. Strengthening regional governance and institutional coordination is therefore essential to improve legal protection for Indonesian Hajj pilgrims.